UPAYA KEPOLISIAN KHUSUSNYA DI POLSEK KONGBENG UNTUK MENANGGULANGI KASUS PERJUDIAN YANG MARAK TERJADI - Febrianto Lembang (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Gambling has existed since ancient times as the development of human civilization. The Encyclopedia of Britanica notes that gambling has been discovered since primitive times, for example the Bushmen in South Africa, Aboriginal tribes in Australia and Indian tribes in America, where they have known the dice game. Then gambling developed since the days of Ancient Greece. A variety of gambling games and techniques that are very easy to make gambling quickly develops throughout the world including Indonesia. The success of the police in overcoming crime must be required by the integrity of various approaches, which can be broadly divided into a penal approach, through the application of criminal law and non-penal measures, namely prevention policies without the application of criminal law, but rather emphasized on various social policies. This is motivated by the fact that crime is a social problem and a human problem. The background of the problem described by the author is as follows: (1) How is the Efforts Made in Countering Gambling Crimes in the Kongbeng District Police Station? (2) Obstacles Faced in Overcoming Gambling in the Kongbeng District Police Station? Based on the results of the previous discussion above, conclusions can be drawn according to the main issues as follows: (1) The role of the Police in tackling gambling crimes in the area of Kongbeng District can be seen from the efforts made by the police, both pre-emptive, preventive, and repressive. In pre-emptive efforts the police do so by instilling good values / norms to the public through the delivery of messages of security and public order (kamtibmas) in mosques, Bhayangkara coaches, security and public order (Bhabinkamtibmas) Door to Door, and legal counseling at village offices / houses of community leaders. In a preventive effort the police conduct patrols and supervision regularly and continuously. Whereas in repressive efforts the police together with the prosecutors and the court conducted an investigation, investigation, prosecution, and the imposition of criminal sanctions; (2) The obstacles experienced by Boyolali Police in uncovering the modus operandi of gambling crime, among others: there are still many people who like gambling, lack of awareness and community participation in providing information about gambling, the more organized the modus operandi that is carried out by the perpetrators gambling crime, limited or lack of personnel to carry out operations or raids and coupled with a lack of support facilities owned by the police. Keywords: Gambling, Countermeasures, Police Efforts